Rethinking women's education from the perspective of Siti Walidah - Nurlaelah; Suharsiwi; Husnul Haq (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This study explores the role of Siti Walidah as a prominent figure in the women's movement in the field of education in Indonesia. It examines the concept of women's education from her perspective, particularly through her founding of the women’s organization ‘Aisyiyah, which operates in the areas of religion, social affairs, economy, and education. The purpose of this research is twofold: to describe Siti Walidah’s perspective on women's education and to outline her contributions in advancing education through ‘Aisyiyah. This research employs a library-based approach, utilizing various sources such as books, journals, documents, dictionaries, magazines, encyclopedias, and other relevant materials. The study involves a textual analysis of Siti Walidah’s educational thoughts, focusing especially on her approach to women’s education. It is analytical descriptive in nature, aiming to objectively present and interpret the actual conditions related to the subject of the study. The findings indicate that Siti Walidah’s advocacy for women’s education included several significant initiatives: founding a religious study group known as Sopo Tresno, teaching women in Kauman to read the Qur'an, and establishing the Maghribi School, a religious study group specifically for women held during the Maghrib prayer time.